How Tupanvirus Degrades the Ribosomal RNA of Its Amoebal Host? The Ribonuclease T2 Track - Rolland, Clara; La Scola, Bernard; Levasseur, Anthony (Frontiers in Microbiology, 2020)
Tupanviruses are giant viruses recently discovered in Brazil from extreme environments: Tupanvirus Soda lake and Tupanvirus Deep Ocean. Unexpected features in Tupanviruses is the cytotoxic effect observed during infection, where the virus degrades the ribosomal RNA of its amoebal host. Interestingly, only Tupanvirus Soda Lake causes this ribosomal RNA shutdown. We performed a genomic comparison of the two strains to determine potential modifications explaining the absence of ribosomal RNA degradation by Tupanvirus Deep Ocean. Whole genome comparisons were performed as well as more in-depth analysis at the gene level. We also calculated selective pressure on the orthologous genes between the two viruses. Our computational and evolutionary investigations revealed a potential target: a ribonuclease T2. These enzymes are known to be involved in cellular RNA catabolism such as in lysosomal degradation of ribosomal RNA. Our results suggest a functional ribonuclease localised in acid compartment closely related to ribonuclease T2 from eukaryotes. Silencing of the RNAse T2 gene of Tupanvirus Soda Lake abolished its ribosomal RNA shutdown ability thereby correlating in silico assumption to the experimental evidence. In conclusion, all our results pointed to RNAse T2 as a target for explaining the difference for rRNA degradation ability between both strains.